2010
DOI: 10.5194/acpd-10-2915-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights into secondary organic aerosol formed via aqueous-phase reactions of phenolic compounds based on high resolution mass spectrometry

Abstract: Abstract. Recent work has shown that aqueous-phase reactions of phenolic compounds – phenol (C6H6O), guaiacol (C7H8O2), and syringol (C8H10O3) – can form secondary organic aerosol (SOA) at high yields. Here we examine the chemical characteristics of this SOA and its formation mechanisms using a High-Resolution Time-of-Flight Aerosol Mass Spectrometer (HR-AMS), an Ion Chromatograph (IC), and a Total Organic Carbon (TOC) analyzer. The phenolic SOA are highly oxygenated with oxygen-to-carbon (O/C) ratios in the r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
72
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 45 publications
5
72
0
1
Order By: Relevance
“…The O:C ratios observed for the aqSOA in this study are around 0.61-0.62 as calculated with the Aiken ambient (AA) method (Table 1). The corresponding ambient improved (AI) O:C ratios (0.81-0.84) are similar to the AI O:C ratio of aqSOA obtained from laboratory oxidation of phenolic compounds (13,16). Enhanced O:C ratios (AA O:C > 0.52) have also been reported for laboratory-generated SOA from the photooxidation of organic precursors in the aqueous phase (14,20).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The O:C ratios observed for the aqSOA in this study are around 0.61-0.62 as calculated with the Aiken ambient (AA) method (Table 1). The corresponding ambient improved (AI) O:C ratios (0.81-0.84) are similar to the AI O:C ratio of aqSOA obtained from laboratory oxidation of phenolic compounds (13,16). Enhanced O:C ratios (AA O:C > 0.52) have also been reported for laboratory-generated SOA from the photooxidation of organic precursors in the aqueous phase (14,20).…”
Section: Discussionsupporting
confidence: 73%
“…S4). The guaiacol dimer is a phenolic species directly emitted during lignin combustion, but it can also be formed in atmospheric liquid water through radical recombination of the guaiacol monomer (13,16). Concentrations of other phenols and anhydrosugars measured by GC/MS (vanillin, vanillic acid, syringol, syringic acid, pyrogallol, and levoglucosan) that are typical tracers of wood combustion emissions (10) covary with the HR-ToF-AMS guaiacol dimer signal (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, FTIR and AMS studies identified the contribution of gas-phase ammonia in the formation of secondary organic nitrate (O'Brien et al, 2013), gave insights into oligomerization chemical mechanisms involved in the formation of biogenic SOA (Russell et al, 2011), and identified phenols as precursors of aqueous SOA (Sun et al, 2010). The analysis of aqueous SOA with FT-IR and H-NMR indicated that different chemical mechanisms occur during processing in cloud and in wet aerosol particles (George et al, 2015;Gilardoni et al, 2016).…”
mentioning
confidence: 99%